A Hybrid Architecture for Experimentation in Wireless Sensor Networks - Silvano, Gilles; Silva, Ivanovitch; Oliveira, Leonardo; Pinheiro, Marcos; Ferreira, Bruno (Anais do Simpósio Brasileiro de Engenharia de Sistemas Computacionais (SBESC); 2016: Anais do VI Simpósio Brasileiro de Engenharia de Sistemas Computacionais, 2016)
Wireless sensor networks is an emerging technology which can be applied for many scenarios. However, many of them have stringent requirements since performance is a limitation for deployment. The solution for this challenge can be carried out by costly and reliable testbeds for conducting tests on prototypes. On the other hand, a more cost-effectiveness approach based on simulation can achieve similar results with the drawback of using non-real firmware. Thus, this work aims to purpose a new hybrid architecture Based on Linux kernel modules for virtualization and emulation of real Wireless sensor networks. This approach assumes that the devices are in conformance with IEEE 802.11, however, other protocols can be used, like IEEE 802.15.4. Real firmware found in a typical IEEE 802.11 devices is adopted to achieve more accurate results.